Limited long term effects of a management programme for heart failure. Issue 9 (13th August 2004) - Mejhert, M; Kahan, T; Persson, H; Edner, M
Abstract : Objective: To evaluate the effects of a nurse based outpatient management programme for elderly patients discharged with heart failure from a university hospital. Design: Patients with heart failure (New York Heart Association class II–IV) and left ventricular systolic dysfunction aged 60 years or more were randomly assigned to follow up within the management programme or to conventional follow up, usually in primary care. Of the 208 participants, 58% were men, mean age was 75 years, and mean ejection fraction 34%. All patients were scheduled for three observational study visits at six month intervals. The primary end point was quality of life (QoL) and secondary end points were hospitalisation and mortality. Results: More patients achieved target doses of angiotensin converting enzyme (ACE) inhibitors in the intervention group than in the control group (82% v 69%, 88% v 69%, and 88% v 74% of recommended target doses at 6, 12, and 18 months of follow up, respectively, p < 0.05 for all). Patients with initial low QoL had a poor prognosis. After a mean 1122 days of follow up, 82% of all patients had been readmitted. There were on average 4.7 readmissions per patient and 66% were due to non-cardiac diagnoses. There were no differences in QoL or health care consumption between the two study groups during follow up. Conclusion: A nurse based management programme is more effective than follow up in primary care in optimising medication for elderly patients with heart failure. However, such a programme does not seem to have a favourable influence on QoL or readmission rate during long term follow up.